Effect of Quadriceps Muscle Strengthening Exercise on Quadriceps and Hamstring Muscle Strength Ratio in Patients with Osteoarthritis Grade 2 and 3 - Thomas Sintong Pratama Purba; Marina Annette Moeliono; Sunaryo Barki Sastradimadja (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To evaluate the effect of quadriceps muscle strengthening exercise on quadriceps and hamstring strength ratio in knee osteoarthritis (OA). Methods: This was a quantitative study with quasi-experimental design. The subjects in the study were 16 female patients with knee OA grade 2 and 3. Quadriceps muscle strengthening exercise was given to the subjects 3 times a week during 8 weeks. The study was conducted at the Department of Physical Medicine and Rehabilitation of the Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin General Hospital in August–September 2015. Results: It was revealed that the quadriceps muscles improved significantly. However, the hamstring muscles did not show significant improvement based on the comparison between before and after performing the exercise. The average right quadriceps muscle strength before exercise was 12.46 and after exercise was 18. The average left quadriceps muscle strength before and after exercise were 11.59 and 17.7, respectively. The average right hamstring muscle strength before and after exercise were 7.29 and 7.94, respectively. Conclusions: There are quadriceps muscle strength improvements after practicing quadriceps muscle strengthening exercise. However, no significant hamstring muscle strength improvement is seen after practicing quadriceps muscle strengthening exercise. An improvement in quadriceps and hamstring muscle ratio is observed. Keywords: Osteoarthritis, quadriceps and hamstring muscle strength ratio, quadriceps muscle strengthening exercise DOI: 10.15850/ijihs.v5n2.1041